Physico-chemical characterization, metabolomic profile and in vitro antioxidant, antihypertensive, antiobesity and antidiabetic properties of Andean elderberry (Sambucus nigra subsp. peruviana) - Porras-Mija I. (2020)
BACKGROUND: The consumption of fruits, mainly berries, has been associated with beneficial health properties. These properties would be related to the quantity and quality of the metabolites present. Some native berries from the Andes, such as Andean elderberry, would be an important source of metabolites with bioactive properties. OBJECTIVES: To evaluate at the physico-chemical and metabolomic level the characteristics of the elderberry from four different high Andean regions, and to determine their bioactive potential through in vitro tests. RESULTS: Significant differences were found in the evaluated characteristics according to the Region of procedence of the fruit. Glucose was the main sugar for all berry samples, followed by fructose. Among the most important organic acids, citric and malic acid were found. Elderberry from Apurimac presented the highest content of total sugars and lower content of total acids in comparison to the samples from other procedences. UPLC-PDA results indicate that Junin elderberries presented the highest value of total phenolic compounds with high contents of flavonols, hydroxycinnamic acids and anthocyanins. Andean elderberry presented cyanidin 3-O-glucoside and cyanidin 3-O-sambubioside as main anthocyanins as well as their respective isomers. All samples showed inhibition activities against the different evaluated enzymes. Elderberries from Apurimac and Junin, displayed the lowest values of IC50 for the inhibition of -amylase and -glucosidase, while for the inhibition of lipase and angiotensin converting enzyme (ACE-I) elderberries from Junin displayed the lowest IC50 values. CONCLUSIONS: The results of this study suggest that Andean elderberry could be considered as an important source of bioactive compounds with properties that could be highlighted by the nutraceutical and functional food industries. © 2020 - IOS Press and the authors. All rights reserved.